2000
DOI: 10.1007/bf02494892
|View full text |Cite
|
Sign up to set email alerts
|

Dramatic solvent effect on the volume of the Diels-Alder reaction between tetracyanoethylene and cyclopentadiene

Abstract: The partial molar volumes (V) and the enthalpies of dissolution (Adis/'~ for tetracyanoethylene, cyclopentadiene, and their Diels--Atder adduct were determined at 25 ~ Eleven solvents of the ~-and n-donor type were used. The use of alkylbenzenes as solvents t'or tetracyanoethylene induces pronounced changes in the enthalpy of dissolution (up to 26 kJ tool -l) and in the partial molar volume (up to I I cm 3 tool-I), whereas these parameters for the adduct change slightly. The V and ,5,jisH values for cyclopenta… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
4
0

Year Published

2009
2009
2021
2021

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 16 publications
0
4
0
Order By: Relevance
“…Thus, the partial molar volumes of the adduct formed from maleic anhydride with trans ‐1‐methoxybutadiene are as follows: 144.6 in nitromethane; 137.0 in acetonitrile; 142.6 in 1.2‐dichloroethane; 134.7 in 1‐chlorobutane, and 139.7 cm 3 mol −1 in dimethyl carbonate 31. Large solvent effects on the partial molar volumes of adduct 7 formed from tetracyanoethylene and cyclopentadiene were noted as well in benzene, 159.6; toluene, 158.3; o ‐xylene, 160.2; mesitylene, 159.4; chlorobenzene, 159.6; acetonitrile, 150.6; ethyl acetate, 150.3; cyclohexanone, 157.5; 1,4‐dioxane, 151.6; dichloromethane, 153.7; and 1,2‐dichloroethane, 154.7 cm 3 mol −1 32. These data illustrate the large differences in the partial molar volumes of cycloadducts, up to 10 cm 3 mol −1 , which are not related with the solvent polarity or donor–acceptor properties.…”
Section: Resultsmentioning
confidence: 93%
See 1 more Smart Citation
“…Thus, the partial molar volumes of the adduct formed from maleic anhydride with trans ‐1‐methoxybutadiene are as follows: 144.6 in nitromethane; 137.0 in acetonitrile; 142.6 in 1.2‐dichloroethane; 134.7 in 1‐chlorobutane, and 139.7 cm 3 mol −1 in dimethyl carbonate 31. Large solvent effects on the partial molar volumes of adduct 7 formed from tetracyanoethylene and cyclopentadiene were noted as well in benzene, 159.6; toluene, 158.3; o ‐xylene, 160.2; mesitylene, 159.4; chlorobenzene, 159.6; acetonitrile, 150.6; ethyl acetate, 150.3; cyclohexanone, 157.5; 1,4‐dioxane, 151.6; dichloromethane, 153.7; and 1,2‐dichloroethane, 154.7 cm 3 mol −1 32. These data illustrate the large differences in the partial molar volumes of cycloadducts, up to 10 cm 3 mol −1 , which are not related with the solvent polarity or donor–acceptor properties.…”
Section: Resultsmentioning
confidence: 93%
“…It is necessary to note that for different planar structures of dienes and dienophiles (except tetracyanoethylene), with the surfaces accessible for solvation, usually weak variety of the solvent effects on the values of partial molar volumes were observed 24,30. On the other hand, the large differences of the partial molar volumes for the branched molecular structure of adducts were detected 6–8,31,32. Thus, the partial molar volumes of the adduct formed from maleic anhydride with trans ‐1‐methoxybutadiene are as follows: 144.6 in nitromethane; 137.0 in acetonitrile; 142.6 in 1.2‐dichloroethane; 134.7 in 1‐chlorobutane, and 139.7 cm 3 mol −1 in dimethyl carbonate 31.…”
Section: Resultsmentioning
confidence: 99%
“…Solvent effects on hetero-DA reactions have been extensively reported in the literature, showing, in general, linear correlations between various reaction properties (e.g., rate constants, endo / exo selectivity) and solvent characteristic parameters such as the acceptor number, H-bond acidity, and density . Kiselev et al exemplified such solvent effects on the molar volume and the enthalpy of solution for several cycloaddition reactions involving TCNE. An interesting theoretical study by Yamabe et al showed that the DMB + TCNE reaction proceeds through an asymmetric TS if the reaction is carried out in methylene chloride, even though both the diene and the dienophile are substituted symmetrically.…”
Section: Introductionmentioning
confidence: 98%
“…It is well known [1,4,[9][10][11] that the rate of isopolar DAR is weakly dependent (if any) on the polarity of the medium. Only a strong donor-acceptor interaction, which is observed, for example, for π -acceptor tetracyanoethylene in the medium of π -donors (alkylbenzenes), significantly reduces the activity of dienophile and its rate in the direct reaction [4,[11][12][13][14]. However the reaction rates of the adduct 11 decomposition are insensitive to the properties of the solvent [11].…”
mentioning
confidence: 93%